0034 Unfair commercial practices in the food supply chain - Cazorla González, María José (Przegląd Prawa Rolnego, 2023)
The aim of this article was to provide an overview of unfair market practices in the food supply chain. In order to achieve this objective relevant European Union and Spanish legal provisions were analysed. Next, successive stages of the agri-food chain and the legal forms of the protection of competition at each of these stages have been presented, followed by a postulate to implement at each of them legislative and fiscal measures that would increase the competitiveness of food producers. In this way agricultural associations could achieve a higher degree of integration and in consequence increase the bargaining power in the market, strengthening their position in the food chain.